2016
DOI: 10.1016/j.math.2016.05.120
|View full text |Cite
|
Sign up to set email alerts
|

Measures of upper limb function for people with neck pain: A systematic review of measurement and practical properties

Abstract: There is a strong relationship between neck pain (NP) and upper limb disability (ULD). Optimal management of NP should incorporate upper limb rehabilitation and therefore include the use of an ULD measure in the assessment and management process. Clear guidance regarding the suitability of available measures does not exist. The aim of this study was to identify all available measures of ULD for populations with NP, critically evaluate their measurement properties and finally recommend a list of suitable measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…The use of different questionnaires makes the comparison of the results between studies somewhat difficult since focus, content, and assessment criteria might differ in some respects [5,6]. Some previous reviews on ASH questionnaires have been reported [7][8][9][10][11]. The included questionnaires in those reviews were not all PROMS and they focused on different areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of different questionnaires makes the comparison of the results between studies somewhat difficult since focus, content, and assessment criteria might differ in some respects [5,6]. Some previous reviews on ASH questionnaires have been reported [7][8][9][10][11]. The included questionnaires in those reviews were not all PROMS and they focused on different areas.…”
Section: Introductionmentioning
confidence: 99%
“…When looking into the methods and checklists that were used to estimate the quality of the included questionnaires, two of the identified previous reviews [9,10] were merely descriptive and no analysis or checklist for quality estimation was used. The three remaining reviews [7,8,11] used different instruments for quality estimation. The first [7] used the COnsensus-based Standards for the selection of health Measurement Instruments, the COSMIN checklist [19].…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental component of monitoring outcomes is having reliable and valid tools with known measurement properties 13 20. While recent research has investigated the psychometric properties of patient-reported outcomes in people with neck pain,13 21 there is a gap in knowledge with respect to performance-based functional outcomes. The purpose of this systematic review was to identify and synthesise clinical measurement studies that evaluate measurement properties of performance-based functional tests in patients with neck disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is consistent with research demonstrating a relationship between cervicothoracic dysfunction and painful upper extremity conditions. 1,5,35,38,39,49 For example, a recent cohort study 42 reported that youth baseball players with a kyphosis measure of >30° had a 2.5-times greater odds of developing medial elbow injuries. This lends credence to the notion that spinal mobility impairments contribute to shoulder and elbow problems in throwing athletes.…”
mentioning
confidence: 99%